Development of a Microcontroller-Based Detection Tool for Repulsion Failure in Long Jump (Dekto-LJ) - Irawan, Yoga; Ditya Candra, Adiska Rani (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
Science and technology are rapidly advancing, particularly in athletics. Currently, in the long jump event, repulsion failure detection still relies on manual plasticine. Therefore, it is necessary to develop an automatic detection tool to assist the referee's performance. The objective of this study is to design a product for failure detection tools in the long jump and to determine their functionality. This study employs a development methodology and utilizes both quantitative and qualitative data analysis. The research participants include students, athletes, and coaches, and the research instrument is a questionnaire. The end product is a sensor for detecting repulsion failure in long jump. The validation of the initial product design by athletic experts yielded an average rating of 77% 'Good', while electronics experts rated it 86% 'Very Good'. The second product design validation received an average rating of 85% 'Very Good' from athletic experts and 90% 'Very Good' from electronics experts. In small-scale trial 1, 84.75% of athletes and 84.33% of coaches rated the product as 'Very Good'. In small-scale trial 2, 87.91% of athletes and 87% of coaches rated the product as 'Very Good'. In the large-scale trial, the product was rated as 'Very Good' by 89.04% of athletes and 90.67% of coaches. The research concludes that the developed tool can detect repulsion failure when the athlete steps on the sensor. It is feasible to develop a repulsion failure detection tool for the long jump to assist the referee in determining repulsion failure.Science and technology are rapidly advancing, particularly in athletics. Currently, in the long jump event, repulsion failure detection still relies on manual plasticine. Therefore, it is necessary to develop an automatic detection tool to assist the referee's performance. The objective of this study is to design a product for failure detection tools in the long jump and to determine their functionality. This study employs a development methodology and utilizes both quantitative and qualitative data analysis. The research participants include students, athletes, and coaches, and the research instrument is a questionnaire. The end product is a sensor for detecting repulsion failure in long jump. The validation of the initial product design by athletic experts yielded an average rating of 77% 'Good', while electronics experts rated it 86% 'Very Good'. The second product design validation received an average rating of 85% 'Very Good' from athletic experts and 90% 'Very Good' from electronics experts. In small-scale trial 1, 84.75% of athletes and 84.33% of coaches rated the product as 'Very Good'. In small-scale trial 2, 87.91% of athletes and 87% of coaches rated the product as 'Very Good'. In the large-scale trial, the product was rated as 'Very Good' by 89.04% of athletes and 90.67% of coaches. The research concludes that the developed tool can detect repulsion failure when the athlete steps on the sensor. It is feasible to develop a repulsion failure detection tool for the long jump to assist the referee in determining repulsion failure.